Towards multi-disciplinary HIV cure research: integrating social science with biomedical research - Grossman, Cynthia I (Trends Microbiol, 2015)
The quest for a cure for HIV remains a timely and key challenge for the HIV research community. Despite significant scientific advances, current HIV therapy regimens do not completely eliminate the negative impact of HIV on the immune system; and the economic impact of treating all people infected with HIV globally, for the duration of their lifetimes, presents significant challenges. This article discusses, from a multi-disciplinary approach, critical social, behavioral, ethical, and economic issues permeating the HIV cure research agenda. As part of a search for an HIV cure, both the perspective of patients/participants and clinical researchers should be taken into account. In addition, continued efforts should be made to involve and educate the broader community.